Insomnia symptoms among individuals with osteoarthritis and symptoms indicative of osteoarthritis: A population-based cross-sectional study using the CLSA. - Melissa Cavallo; Elizabeth M Badley; Anthony V Perruccio (PLoS ONE)
Objective To compare the prevalence and examine the likelihood of insomnia symptoms in middle- and older-aged adults with an osteoarthritis (OA) diagnosis and with joint symptoms indicative of OA but without a diagnosis, in a population-based sample. Methods Data are from the Canadian Longitudinal Study on Aging (participants aged >45). Individuals reported on doctor-diagnosed OA (hand, hip, or knee) and joint symptoms typical of OA, irrespective of OA diagnosis. A three-level 'OA-status' variable was derived: diagnosed OA; joint symptoms-no OA; no symptoms-no OA (controls). Participants responded to sleep-related questions and were categorized as experiencing insomnia symptoms (yes/no). Logistic regression analysis examined the association between insomnia symptoms and OA status, adjusting for a number of covariates. Results Of 21,422 respondents, OA was reported by 29.1% (mean age 68.2) and 17.2% reported joint symptoms-no OA (mean age 63.9). One third of those with diagnosed OA and with joint symptoms-no OA reported insomnia symptoms compared to a quarter of controls. Those with OA and with joint symptoms-no OA were similarly more likely to report insomnia symptoms than controls (odds ratio (OR) 1.25, 95% CI 1.17-1.35 and OR 1.32, 95% CI 1.21-1.43). Also significantly associated with insomnia symptoms were female sex, current smoker, lower activity level, multiple chronic conditions and depressive symptoms. Odds ratio magnitudes were greatest for depressive symptoms (OR 2.50, 95% CI 2.26-2.76), comorbidity count (3 + vs. 0 OR 1.68, 95% CI 1.47-1.91) and female sex (OR 1.46, 95% 1.37-1.55). Conclusion Insomnia symptoms were not uncommon among comparatively younger individuals with typical OA joint symptoms and those with OA. This suggests that healthcare providers should address sleep-related issues in those consulting for joint pain, irrespective of diagnosis. Given their high prevalence, this also has implications for sleep-related issues at a population level.